1999
DOI: 10.1002/(sici)1522-9505(19990601)267:1<73::aid-apmc73>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

New analytical methods for epoxy resins, 1. Liquid chromatography at the critical point of adsorption and MALDI-TOF mass spectrometry

Abstract: The analysis of bisphenol A based epoxy resins by size exclusion chromatography, liquid chromatography at the critical point of adsorption and MALDI‐TOF mass spectrometry with respect to molar mass, functionality, and branching is described. For obtaining proper molar masses, size exclusion chromatography must be calibrated by a combined calibration curve based on polystyrene and epoxy resin oligomers. Liquid chromatography at the critical point of adsorption yields quantitative data on different functionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Several epoxy resins were used, having at least nominally the structure of diglycidyl ethers. Pasch et al7 analyzed by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) epoxy resins (technical products provided by Dow Deutschland, Inc., Rheinmünster, Germany) and established that there are several structural imperfections. Depending on the source of the epoxy resins, these imperfections could differ, as the manufacturing processes also differ.…”
Section: Resultsmentioning
confidence: 99%
“…Several epoxy resins were used, having at least nominally the structure of diglycidyl ethers. Pasch et al7 analyzed by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) epoxy resins (technical products provided by Dow Deutschland, Inc., Rheinmünster, Germany) and established that there are several structural imperfections. Depending on the source of the epoxy resins, these imperfections could differ, as the manufacturing processes also differ.…”
Section: Resultsmentioning
confidence: 99%
“…The used salt and matrix were lithium chloride (LiCl) and dihydroxybenzoic acid (DHB, Adrian et al 1999;Pasch et al 1996). The epoxy novolac resin was first solved in tetrahydrofuran (THF) and a LiCl/H 2 O solution was added.…”
Section: Maldi-tof Measurementsmentioning
confidence: 99%
“…Having a deeper look into the mass spectra additional distributions with also a repeating unit of 325 Da are observed. Related to the synthesis of the epoxy novolac resin the following reaction can take place (Adrian et al 1999):…”
Section: Maldi-tof Measurementsmentioning
confidence: 99%
“…The analysis of bisphenol A based epoxy resins by size exclusion chromatography (SEC), liquid chromatography at the critical point of adsorption (LC-CC) and MALDI-TOF mass spectrometry with respect to molar mass, functionality, and branching has been described in part 1 of this paper 2) . It has been shown that LC-CC yields quantitative data on different functionality fractions, including fully epoxydized, glycidyl-diol and bisdiol oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…Contour plots of the 2D separation; 1st dimension: LC-CC, 2nd dimension: SEC; detection: UV 280 nm; (a) sample 8, (b) sample 7, (c) sample 6; for regions(1,2,3,4) and series (a, b, c) see text.…”
mentioning
confidence: 99%